2020
DOI: 10.6065/apem.1938156.078
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid in Korean children and adolescents: reference percentiles and association with metabolic syndrome

Abstract: To establish age/sex-specific reference intervals for serum uric acid and to examine the associations between serum uric acid level and metabolic syndrome (MetS) and its components in Korean children and adolescents. Methods: We analyzed data for 1,349 subjects aged 10 to 19 years from the Korea National Health and Nutrition Examination Survey 2016-2017. Results: The mean uric acid levels were 5.9±1.3 mg/dL (interquartile range, 5.0-6.8 mg/dL) in males and 4.6±0.9 mg/dL (interquartile range, 3.9-5.2 mg/dL) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Elevated uric acid levels contribute to the development of adverse conditions. Previous results suggest a strong association between uric acid levels and metabolic syndrome in children and adolescents, and various mechanisms have been proposed to explain this correlation (31). HDL-C has the effects of reverse transport of cholesterol to reduce atherosclerosis, anti-inflammation, anti-thrombosis, antiapoptosis, and vasodilation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated uric acid levels contribute to the development of adverse conditions. Previous results suggest a strong association between uric acid levels and metabolic syndrome in children and adolescents, and various mechanisms have been proposed to explain this correlation (31). HDL-C has the effects of reverse transport of cholesterol to reduce atherosclerosis, anti-inflammation, anti-thrombosis, antiapoptosis, and vasodilation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for hyperuricemia have been of interest since hyperuricemia was linked to hypertension, metabolic syndrome, diabetes, kidney disease, and cardiovascular diseases in studies on adults [ 43 , 44 ]. In pediatric populations, serum uric acid concentrations have been associated with abdominal obesity [ 4 , 7 ], high blood pressure [ 6 , 45 47 ], insulin resistance [ 4 ], and metabolic syndrome [ 4 , 7 , 46 ]. In our children’s cohort, BMI z-scores and eGFR, reflective of reflecting kidney function, were significantly related to serum uric acid concentrations ( S2 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Although extracellular uric acid acts as a strong antioxidant, intracellular uric acid acts as a pro-oxidant when it stimulates NADPH oxidase and increases oxidative stress [ 2 ]. Hyperuricemia has been identified as a cause of gout and nephrolithiasis, and its relationship with hypertension, metabolic syndrome, kidney disease, and cardiovascular disease in adult [ 3 ] and pediatric populations has been proposed [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study from Taiwan showed that a high level of uric acid (≥7.3 for males and ≥6.2 mg/dL for females) increased the risk of hypertension in males and females, and metabolic syndrome in male adolescents after 10 years of follow-up [ 57 ]. Cho et al reported that serum uric acid level is positively associated with metabolic syndrome in children [ 58 ]. Accordingly, uric acid might be a useful marker of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%